2015
DOI: 10.1007/s11064-015-1532-2
|View full text |Cite
|
Sign up to set email alerts
|

MCT4-Mediated Expression of EAAT1 is Involved in the Resistance to Hypoxia Injury in Astrocyte–Neuron co-Cultures

Abstract: Hypoxic stressors contribute to neuronal death in many brain diseases. Astrocyte processes surround most neurons and are therefore anatomically well-positioned to shield them from hypoxic injury. Excitatory amino acid transporters (EAATs), represent the sole mechanism of active reuptake of glutamate into the astrocytes and neurons and are essential to dampen neuronal excitation following glutamate release at synapses. Glutamate clearance impairment from any factors is bound to result in an increase in hypoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Because increased accumulation of lipid content in aging SkM could cause progressive sarcopenia (30), the mRNA profile of these genes as induced by dietary epicatechin is noteworthy. In addition, epicatechin-reversed expression of the high-affinity glutamate transporter Slc1a3 , or EAAT1 , was shown to promote resistance to hypoxic injury in astrocyte-neuron cocultures (50); this finding may be relevant to cellular processes of the neuromuscular junction (51) and hence overall SkM function.…”
Section: Discussionmentioning
confidence: 99%
“…Because increased accumulation of lipid content in aging SkM could cause progressive sarcopenia (30), the mRNA profile of these genes as induced by dietary epicatechin is noteworthy. In addition, epicatechin-reversed expression of the high-affinity glutamate transporter Slc1a3 , or EAAT1 , was shown to promote resistance to hypoxic injury in astrocyte-neuron cocultures (50); this finding may be relevant to cellular processes of the neuromuscular junction (51) and hence overall SkM function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the morbidity of PD is greater among older people, it might be associated with age-related conditions such as prolonged ischemia or hypoxia in the brain. There is ample evidence to show that an insufficient blood or oxygen supply to the brain, could attenuate neurons’ resistance to environmental damage, and it can even trigger cell death [5,6,7]. Therefore, hypoxia/ischemia and neurotoxins should also be recognized as critical pathogenic factors that contribute to the development of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that Mcts are involved in the response to hypoxia and ischemia. For example, hypoxic preconditioning caused an upregulation of Mct4 in rat astrocytes [45] and a knockdown of Mct4 interfered with the survival of mixed astrocyte-neuron cultures under hypoxia [46]. Mct4 activity and structure appear to be associated to the astrocyte-specific excitatory amino acid transporter 1 (Eaat1) [47].…”
Section: Discussionmentioning
confidence: 99%